HEALTH EDUCATION TO SOCIETY PERCEPTION (THE PRINCIPAL CONSTRUCTION OF FAMILY WELFARE) ABOUT HIV/AIDS (Studies In Besuk Kidul Village Besuk Distric Probolinggo) - Dhara Retno Juwita; M. Zainul Arifin; . Suhardono (Jurnal Keperawatan, 2012)
AIDS is a collection of symptoms caused by decreasing the body's immunity as a result of Human Imunodeficiency Virus (Dinkes, 2012). Most sufferers of HIV/AIDS get a negative perception from the family and social environment. Increased patient of HIV/AIDS and lack of health education about HIV/AIDS make people become overly cautious, so they assume that HIV/AIDS very dangerous and patient of HIV/AIDS can no longer socialize with people of normal health status. The purpose of this study was top analyze the influence of health education on the perception of society (The principal construction of family welfare) about HIV/AIDS in the village of Besuk Kidul, district of Besuk, Probolinggo regency.This research design used one group pre-post test design, with the population of all The principal construction of family welfare in the village of Besuk Kidul, by total sampling with respondents as many as 40 people. The independent variable was health education about HIV/AIDS and the dependent variable was the perception of society (The principal construction of family welfare) about HIV/AIDS. The Instrument of this research used a questionnaire, then analized by editing, coding, scoring, tabulating and statistic T-Test with an error level 0.05.The result of research obtained that the perception of society (The principal construction of family welfare) about HIV/AIDS before being conducted health education was positive as 55% and negative as 45%, after being conducted health education the perception of society about HIV/AIDS was positive as 73% and negative as 27%. The analize result used T-Test obtained significant 0.000, so it can be ctated that H1 accepted.The conclusion of this research showed that there is an influence of health education to perception of society (the principal construction of family welfare) about HIV/AIDS in the village of Besuk Kidul district of Besuk Probolinggo regency.